Application of a wheel cleaning system during grinding of alumina with minimum quantity lubrication - Lopes, Jose C. [UNESP]; Ventura, Carlos E. H.; Fernandes, Lucas de M. [UNESP]; Tavares, Andre B. [UNESP]; Sanchez, Luiz E. A. [UNESP]; Mello, Hamilton J. de [UNESP]; Aguiar, Paulo R. de [UNESP]; Bianchi, Eduardo C. [UNESP] (Springer, 2019)
High thermal loads generated during grinding of ceramic materials increase abrasive tool wear and damage workpiece quality. In this regard, the application of cutting fluid has been mandatory, although several researchers have been working to reduce oil consumption in such processes, as it increases the cost of the final product and is harmful to both people and environment. Among the alternatives, minimum quantity lubrication (MQL) has been increasingly investigated, even though clogging of the grinding wheel is prone to occur. In order to improve the cleaning of the abrasive tool during the process and reduce oil consumption, this paper proposes the investigation of the performance of MQL technique applied together with a wheel cleaning system, which consists of a compressed air jet directed to the wheel surface, during grinding of alumina. Different direction angles of the air jet were tested and conventional flood coolant as well as MQL alone were applied for comparison purposes. Flood coolant was the most efficient method regarding cleaning of the grinding wheel, decrease of diametral wheel wear, surface roughness, and average power followed by the use of MQL with an air jet directed to the wheel surface with an angle of 30 degrees. This latter arrangement, however, can become an option when the reduction of oil consumption is a priority, as it provides the best results when compared to the other air jet direction angle configurations.
Keywords: Plunge grinding; Diamond wheel; Alumina; Minimum quantity lubrication; Wheel cleaning system